A REVIEW OF VERTEBRATE BEAK MORPHOLOGIES IN THE TRIASSIC; A FRAMEWORK TO CHARACTERIZE AN ENIGMATIC BEAK FROM THE ISCHIGUALASTO FORMATION, SAN JUAN, ARGENTINA (Ameghiniana, 2020)
Beaks are an edentulous dietary modification present in numerous forms in turtles, birds, cephalopods, and some actinopterygian fishes today. Beaks have a rich fossil record and have independently evolved at least nine times over the past 300 million years in early reptiles, dinosaurs and their relatives, and crocodile and mammal relatives. Here, we focus on the earliest evolution of beaks in the reptile fossil record during the Triassic Period (252–201.5 million years ago). We analyze the phylogenetic distribution of Triassic beaks and review their morphologies to create a framework to estimate beak similarity. With this, we describe a unique fossil beak (PVSJ 427) from the Late Triassic Ischigualasto Formation, San Juan, Argentina, and place it in our similarity analysis alongside other vertebrate clades from the Triassic Period, or with Triassic origins. PVSJ 427 is a small iron-rich cast fossil that is triangular with a concave midline shelf, rounded lateral walls, and an anterior point. No clear synapomorphies are present in PVSJ 427, and as such, its phylogenetic position is not inferred herein. Some remnants of bone are recognizable in thin sections of PVSJ 427, indicating that it likely represents a bony beak replaced by minerals. The morphology of PVSJ 427 is most similar to the predentary, an edentulous element restricted to ornithischian dinosaurs, although this specimen is approximately three times larger than the earliest known ornithischian predentaries. Regardless of phylogenetic position, PVSJ 427 reflects an early evolution of a predentary-like beak and indicates that this animal was ecologically convergent with the earliest ornithischian dinosaurs.